Empowering communities through the sustainable transformation of used cooking oil waste into aromatherapy candles: A holistic approach to waste management - Nurul Shofiah; Husna Malikatus Siswanto; Novita Ramadhanfi Maulani; Suwito Setyo Wicaksono (Universitas Muhammadiyah Malang, 2025)
Used cooking oil from household frying is often discarded improperly, leading to environmental pollution. One sustainable solution is repurposing it into aromatherapy candles, reducing waste while creating economic opportunities. To address this issue, KKM 210 UIN Malang conducted a community service initiative titled